TRADISI ANGALLE ALLO PASCA KEMATIAN PERSPEKTIF SADD DZARIAH (Studi Kasus Di Desa Taeng, Kecamatan Pallangga, Kabupaten Gowa) - Hafid, Eviyanti; Arsyad, Azman (Universitas Islam Negeri Alauddin Makassar, 2020)
AbstractThis study discusses the main issues related to Sadd Dżariah's views in the Angalle Allo tradition in Taeng Village, Pallangga District, Gowa Regency. The purpose of this study, namely: This type of research is qualitative where qualitative research produces a descriptive data, so researchers collect data through interviews, observation and documentation. This research approach uses a sociological approach and shar'i approach. As for the informants in this study are community shops, as well as several communities directly involved in this adat procession. The data analysis techniques in this research process are: Data collection, data reduction, data presentation and drawing conclusions. As for Sadd Dżariah's view of the Angalle Alllo tradition which is included in the category of Acts which is basically permissible because it contains benefits, but allows for interpretations. What is meant by actions that are basically permissible are, carrying out good traditions in accordance with the teachings of Islam contained in QS Al-A'raf / 7 Paragraph 199, gathering together to eat where there is blessing and reciting verses of the Holy Qur'an ' where the reward is very useful for people who have died. While allowing the occurrence of the intended interpretations if in carrying out this tradition with the intention to send food to people who have died, making food in this tradition is mandatory so that it troubles the families of people who have died and other forms of activities that are not recommended in Islam.The implication of this research is to explain about Sadd Dżariah's view of the Angalle Allo tradition preserved by the people of Taeng Village to the present. The conclusions above can be a factor for people to preserve this culture in accordance with Islamic teachings based on the Qur'an and Sunnah. Keywords : Tradition, Angalle All, Death, Sadd Dzariah